Locarno Treaties (1925) in the Context of the Versailles System Transformation as seen from London - E. V. Khakhalkina; V. S. Dzyuba (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
This paper is an attempt to reassess the role of the Locarno Treaties (1925) in terms of the Versailles-Washington system of international relations evolution. The authors argue that the Locarno Treaties represent one of the turning points in the development of the international order after World War I. The Treaties were not a mere add-on to the Versailles system, in fact, they had replaced it and became the main legal instrument for maintaining security in the region. In order to test this hypothesis and provide a better understanding of how the contemporaries themselves assessed these agreements, the authors examine them within a broader context of debates on the European security issues, which took place in the 1920s.The views of the British elites on this matter are of particular interest here, since it was the British diplomacy that was at the origin of the Locarno Conference in 1925. The paper draws on a wide range of recently declassified archival documents, as well as on the materials of the debates in the House of Commons and publications in the leading British newspapers. It allows the authors to trace the evolution of approaches by the main British political parties to security issues in Europe. A systematic comparison of views of the Conservative and the Labour party representatives on the Geneva Protocol and the Rhineland Pact shows that by mid-1920s the British political elites advocated for an in-depth transformation of the Versailles order, particularly, through the development of an effective mechanism for maintaining international security. On that basis a broad political consensus had arisen, which led to the formation of a new two-party structure (Tory-Labour) after World War I.The study begins with an overview of the political situation in Europe and in Great Britain in the early 1920s. Then, it examines the Labour Party’s draft of the Disarmament Protocol, as well as the principal causes of its failure. Finally, the paper covers the preparatory process for and the progress of the Locarno negotiations. Special attention is paid to the debates in the House of Commons on the conference, particularly, on its outcome document - the Rhineland Pact.